State and People, Central and Local, Working Together : The Vietnam Rural Electrification Experience - Gencer, Defne (World Bank, Washington, DC, 2017)
This book chronicles the development of Vietnam's rural electrification program. It tells the story of how the Vietnamese government conceived, developed, scaled up, and improved its program. It also discusses the role the government, the countries main utility, local authorities, local communities, and the country's international development partners played in the pursuit of the electrification agenda. The book provides an overview of the strategies that fueled the impressive expansion of access to electricity in Vietnam, the development of the institutions that implemented the program and the passage of policies and laws that made growth of such scale possible. It also discusses results from the ground, and particularly the impacts of electrification on people's lives. It concludes with an attempt to draw lessons from Vietnam's experience. The book comprises three main parts: part A, made up of eight sections, provides an overview of Vietnam's rural electrification experience, which can be divided into six distinct periods. Part B summarizes a select set of findings from the multiyear survey and discusses the impact of rural electrification on Vietnamese households. Part C draws lessons from the experience of rural electrification in Vietnam, based on the information presented in parts A and B. It discusses the lessons learned from the perspectives of the government and the World Bank.